WASC Substantive Change Screening Form: BA Psychology Online (Completion Program)
CSUCI's BA Psychology online degree completion program provides students training in all of the main specializations within psychology through a core course model, while providing opportunities for students to take electives, including supervised internship and research experiences. Many alumni enter into careers and graduate programs in fields related to psychology, social work, business, and law. As an upper division degree completion program, CI will not offer the lower division general education courses or the lower division Psychology core courses via distance education. Students admitted to the program will be upper-division transfer students and must meet the following requirements for admission: •Admissions application at& $70. 00 application feeCalState Apply online•GPA of 2. 0 or higher•Transfer a minimum of 60 semester/90 quarter units for admission (Students must transfer 70 lower-division semesters/105 quarter units to complete the degree)•Golden Four (A1, A2, A3, B4) classes completed with grades of "C-" or better•Three lower division Psychology core courses (Introduction to Psychology, Elementary Statistics/Introductory Statistics, and Developmental Psychology)•Good standing (i. e. eligible to re-enroll) at the last institution attended